Living with food allergies: the experiences of adult patients and caregivers - Santos, Alexandra F.; Worm, Margitta; Kurita, Shoko; Wong, Tania; Contato, Davide; Pirillo, Elia; Esteban, A. Esther; Tassinari, Paolo; Perna, Flavia; Chinthrajah, R. Sharon (Frontiers in Allergy, 2023)
Background Few studies have addressed how food allergy may impact differently on the daily lives of adults with food allergies and caregivers for food-allergic dependents. Objective To explore similarities and differences in life experiences and unmet needs between individuals caring for a child with food allergy and adults with food allergy world-wide. Methods Two multinational, virtual, interactive, moderated discussions of specific questions between respectively people with food allergies and caregivers for people with food allergies, with experienced clinicians participating. Results Sixteen individuals living with food allergies and nine caregivers took part in the two roundtables. Food avoidance and antihistamines were the most common treatments for food-allergic reactions in both groups. Caregivers reported greater burden of disease on affected individuals and families than did adult patients. Adult panelists considered autoinjectors easy to use but caregivers reported additional emotional stress thinking about autoinjector use. Caregivers described an ever-present fear of inattention and of overlooking a risk factor for a severe reaction, whereas adult panelists showed a determination not to let their food allergies interfere with living their lives. Both groups had safety-conscious attitudes to treatments, but adult patients emphasized convenience while caregivers prioritized reduced severity of reactions and eliminated fear. Both groups confirmed the need for improved, trusted sources of information, and for resources and training programs for any new therapies. Conclusion The interactive exchange provided insights into differences between adult patients and caregivers, notably in fear and confidence in daily life, severity of disease impact, and unmet needs for treatments.